Goal-setting and spouse involvement in the treatment of obesity - Dubbert, Patricia M.; Wilson, G.Terence (Behaviour research and therapy, 1984)
Two types of goal-setting (daily vs weekly) and two levels of spouse involvement (couples vs individual treatment) were evaluated in a 19-week behavioral weight-control program. Forty-seven married Ss with spouses willing to participate were randomly assigned to one of four treatments: Couples/Weekly Goals, Couples/Daily Goals, Individual/Weekly Goals, Individual/Daily Goals. At posttreatment, Ss had lost an average of 171b and reduced their percent over ideal weight from 49 to 36%. Losses were maintained at the 6-month clinic follow-up. Weight losses for the two goal-setting conditions and the two spouse treatments did not differ. Improvements were observed in resting pulse, blood pressure and step-test time, and these were maintained at the 6-month follow-up. Adherence to caloric self-monitoring, self-reported exercise adherence and marital satisfaction were significantly correlated with weight loss. Decreases in depression and improvements in body-image satisfaction were also observed. Mail and telephone follow-up at 12 and 30 months posttreatment indicated satisfactory maintenance for the majority of Ss. Factors associated with maintenance and relapse during long-term follow up are discussed.